The use of computer diagnostic apps to assist computer troubleshooting / Mohd Saharudin Abuludin, Norazuwa Salehudin and Beny Yusmar - Abuludin, Mohd Saharudin; Salehudin, Norazuwa; Yusmar, Beny (Faculty of Computer and Mathematical Sciences, 2023)
Electric and electronic equipment have become significant tools in modern human life. One of these is the use of computers, which have proven to be capable of simplifying and solving problems faced by people in their daily activities. Electric and electronic equipment may encounter issues when in use or about to be used. The problems encountered may be easy and can be resolved quickly and independently by the user. Self-help troubleshooting methods have been widely applied to assist individuals in attempting to solve problems based on provided instructions, whether in print or digital format. This innovation digitizes the flowchart for identifying and repairing issues that arise during computer usage. This innovation has resulted in a user-friendly application called the Computer Diagnostic App to help computer users attempt to resolve problems they encounter while using their computers. The design of this application are based on a comprehensive flowchart for identifying computer issues, which can be widely accessed on the web and has become a global reference based on Google search engine findings. A research study are conducted among Information Technology Certificate students at Temerloh Community College to obtain feedback and assess the effectiveness of using this application to resolve issues that arise during computer usage.